A novel transnational fresh oocyte donation (TOD) program based on transport of frozen sperm and embryos. Issue 2 (6th December 2018) - La Marca, A; Dal Canto, M; Buccheri, M; Valerio, M; Mignini Renzini, M; Rodriguez, A; Vassena, R
Abstract: STUDY QUESTION: What is the clinical efficacy of an oocyte donation program based on the transportation of frozen semen and embryos between two countries? SUMMARY ANSWER: The transnational oocyte donation program is efficient and reliable and it could provide a first-line strategy to overcome the lack of donors in some countries. WHAT IS KNOWN ALREADY: While there is increasing need for donated oocytes, in many countries the availability of donors is still insufficient to cover the therapeutic demands, and patients are referred abroad for treatment. Since embryo cryopreservation is reliable and efficient, we propose a strategy based on frozen embryos instead of frozen oocytes to satisfy the increasing demand for cross border oocyte donation. STUDY DESIGN, SIZE, DURATION: This is a retrospective cohort study including 630 patients treated from December 2015 to July 2017. PARTICIPANTS/MATERIALS, SETTING, METHODS: Infertile women were treated with elective vitrified-thawed embryo shipping and embryo transfer (ET) between two IVF clinics, one in Spain and one in Italy. MAIN RESULTS AND THE ROLE OF CHANCE: A total of 2617 embryos were created for the 630 patients and the survival rate after warming was 98.5%. After the first ET the live birth rate (LBR) was 30.6%. In 476 patients (75.5%), embryos were transferred at the cleavage stage (Day 2 or 3) and the LBR was 29.2%. Vitrified blastocysts were available for 154 patients (24.5%) and the LBR was 35%. Among patients who did not achieve a pregnancy after the first frozen ET (FET), 92.5% had at least one frozen embryo for successive procedures. 213 patients underwent a second FET. The LBR at the second FET was 30%. The cumulative LBR at the end of the observation period was 39.3%. LIMITATIONS, REASONS FOR CAUTION: The study design was retrospective. A direct comparison with vitrified oocyte donors cycle and subsequent fresh ET would have permitted to compare this strategy versus the current standard based on vitrified gametes. WIDER IMPLICATIONS OF THE FINDINGS: The LBR found in our study is more than acceptable and seems to be higher than what reported with vitrified oocytes. The transnational fresh oocyte donation program may have several advantages over the shipment of vitrified oocytes: similarly to the fresh oocyte donation program it allows for personalized care in oocyte recipient, which is provided by assigning a flexible number of oocytes, and at the same time it maintains the benefit of a frozen ART program permitting scheduling flexibility. The TOD program is efficient and may be proposed as a first-line strategy for distance and inter-countries oocyte donation programs. STUDY FUNDING, COMPETING INTEREST(S): None. TRIAL REGISTRATION NUMBER: NA.